2014
DOI: 10.1177/070674371405900206
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Enhances the Development of Schizophrenia in First-Degree Relatives of Patients with Schizophrenia

Abstract: Our study provides direct evidence for the causative role of MA use in the etiology of schizophrenia and highlights the role of MA-induced brain abnormalities in cognitive deficiency and development of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Meth is amongst the most used illicit substance in people with schizophrenia (11). Importantly, chronic meth use might promote the development of schizophrenia in at-risk individuals (12,13), and a major animal model to capture some of schizophrenia-like psychotic symptoms relies on chronic meth exposure (14). For example, impairment in prepulse inhibition, a measurement of sensorimotor gating deficits often observed in people with schizophrenia (15), can be elicited following chronic meth exposure in rodents (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Meth is amongst the most used illicit substance in people with schizophrenia (11). Importantly, chronic meth use might promote the development of schizophrenia in at-risk individuals (12,13), and a major animal model to capture some of schizophrenia-like psychotic symptoms relies on chronic meth exposure (14). For example, impairment in prepulse inhibition, a measurement of sensorimotor gating deficits often observed in people with schizophrenia (15), can be elicited following chronic meth exposure in rodents (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…18,46 It has also been shown that methamphetamine abuse in individuals at familial risk causes schizophrenia that persists regardless of whether the drug abuse continues. 16 An extrapolation of these findings 7 The adjusted model includes age, gender, and family history as covariates in addition to controlling for clustering of individuals within families.…”
Section: Discussionmentioning
confidence: 99%
“…Data from adults indicate that genetic liability to stimulant-induced psychosis overlaps with genetic liability for schizophrenia 15 and that stimulants may cause schizophrenia in individuals at familial risk. 16 These findings suggest that the risk of psychotic adverse effects of stimulants may be higher in youth with a family history of mental illness. This contingency could be clinically important because ADHD is more common among offspring of parents with severe mental illness 17 and because psychotic symptoms induced by stimulants may signal long-lasting vulnerability to psychosis.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Alcohol and drug use, particularly cannabis and amphetamine, might initiate psychosis in people susceptible to schizophrenia (Pogue-Geile & Harrow, 1984;Li, Lu, Xiao, Li, He, & Mei, 2014;Medhus, Rognli, Gossop, Holm, Mørland, & Bramness, 2015). Substance abuse is strongly linked to the recurrence of schizophrenia symptoms (Moore, Mancuso, & Slade, 2012).…”
Section: Possible Causes Of Schizophreniamentioning
confidence: 99%